630 Hailey-Hailey Disease: A Rare Presentation in the Hypopharnyx. (19th August 2022) - Tan, CH; Wright, B; Black, M; Devlin, B
Abstract: Background: Hailey-Hailey disease or familial benign pemphigus is a rare genetic blistering skin disease due to mutation of the ATP2C1 gene inherited in autosomal dominant fashion. Prevalence is around 1 in 50, 000 and positive family history is observed in 75% of cases. Patients typically present with well-demarcated painful erosive and yellow-crusted rash in the skin folds, following a relapsing-remitting pattern. There are very limited known cases of extra-dermatological presentation of this disease. Case: 64-year-old gentleman presented with dysphagia, hoarseness, sore throat, dry cough, and intermittent haemoptysis. Initial flexible nasendoscopy showed mild erythema of epiglottis and false cords, post-cricoid oedema and very mild Reinke's oedema. He was treated as acid reflux with omeprazole but to little effect. Endoscopy 4 months later showed similar findings hence biopsy of the hypopharynx was taken. The sample demonstrated intraepithelial clefting, suspicious of intraepithelial vesiculobullous disorder particularly pemphigus vulgaris. Looking into this gentleman's medical history, it was found that he is under the care of dermatology for Hailey-Hailey disease, which he was diagnosed 30 years ago. He also has a strong family history of this condition. Based on the biopsy findings and patient profile, it was concluded that this gentleman has a hypopharyngeal manifestation of Hailey-Hailey disease. Discussion: Hailey-Hailey disease is traditionally described as a dermatological condition. This gentleman is one of the rare few cases of non-dermatological manifestation of this disease.